High-Frequency Isotope Compositions Reveal Different Cloud-Top and Vertical Stratiform Rainfall Structures in the Inland Tropics of Brazil - Santos, V. [UNESP]; Durán-Quesada, A. M.; Sánchez-Murillo, R.; Gastmans, D. [UNESP] (American Geophysical Union (AGU), 2024)
Understanding the key drivers controlling rainfall stable isotope variations in inland tropical regions remains a global challenge. We present novel high-frequency isotope data (5–30 min intervals) to disentangle the evolution of six stratiform rainfall events (N = 112) during the passage of convective systems in inland Brazil (September 2019–June 2020). These systems produced stratiform rainfall of variable cloud features. Depleted stratiform events (δ18Oinitial ≤ −4.2‰ and δ18Omean ≤ −6.1‰) were characterized by cooler cloud-top temperatures (≤−38°C), larger areas (≥48 km2), higher liquid-ice ratios (≥3.1), and higher melting layer heights (≥3.8 km), compared to enriched stratiform events (δ18Oinitial ≥ −3.8‰ and δ18Omean ≥ −5.1‰). Cloud vertical structure variability was reflected in a wide range of δ18O temporal patterns and abrupt shifts in d-excess. Our findings provide a new perspective to the ongoing debate about isotopic variability and the partitioning of rainfall types across the tropics.
Keywords: stable isotopes; stratiform rainfall; tropical inland